Hamstring and other thigh injuries in children and young athletes - Valle, X.; Malliaropoulos, N.; Párraga, J. D.; Bikos,G.; Mónaco, M.; Maffulli, N. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Background: In adults, hamstring injuries may lead to long periods of rehabilitation, and carry a definite risk of recurrence. However, no studies detail how these injuries affect young athletes. Objective: To describe and analyse injuries in the hamstring area in young athletes. To identify risk factors for injuries to the hamstring area in this age group, which will make it possible to design and optimise prevention plans. Methods: The study population consisted of 1157 young athletes with an average age of 13.56 years, all members of the Barcelona Football Club. Injuries to the hamstring area over three consecutive seasons (from July 2007 to June 2010) were analysed. Results: The 50 injuries in the hamstring muscle complex included 14 injuries to the biceps femoris, 17 to the semitendinosus-semimembranosus complex, 10 cases of delayed onset muscle soreness (DOMS), and 9 avulsion of the ischial tuberosity. Hamstring injuries were first identified in young athletes starting from age 9, with an age related increased rate up to the age of 15, and a lower incidence at age 14, 16 and 18. The average time lost following an hamstring injury was 21 days, and 43.4 days following avulsion from the ischium. The highest incidence of injuries occurred in football players. Conclusions: Hamstring injuries in this group of young athletes are less prevalent than in adults.